**Given:**

The sequence is
an+1=4−an for n≥1
. (1)

The first term of the sequence is
a1=1
.

**Calculation:**

Obtain the first five terms of the sequence.

Substitute 1 for *n* in equation (1),

a1+1=4−a1

a2=4−a1
(2)

Substitute 1 for
a1
in equation (2),

a2=4−1=3

Thus, the second term of the sequence is
a2=3
.

Substitute 2 for *n* in equation (1).

a2+1=4−a2

a3=4−a2
(3)

Substitute 3 for
a2
in equation (3),

a3=4−3=1

Thus, the third term of the sequence is
a3=1
.

Substitute 3 for *n* in equation (1),

a3+1=4−a3

a4=4−a3
(4)

Substitute 1 for
a3
in equation (4).

a4=4−1=3

Thus, the fourth term of the sequence is
a4=3
.

Substitute 4 for *n* in equation (1).

a4+1=4−a4

a5=4−a4
(5)

Substitute 3 for
a4
in equation (5).

a5=4−3=1

Thus, the fifth term of the sequence is
a5=1
.

Therefore, the first five terms of the sequence is
{1,3,1,3,1}
.

Here, it is noticed that the terms of the sequence oscillate between 1 and 3.

Hence, the sequence is not convergent.

Therefore, it can be concluded that the sequence is divergent.